Variability of tap water residual chlorine and microbial counts at spatially resolved points of use - Pieri, Panayiota; Andra, Syam S.; Demetriou, George; Zambakides, Nicos; Makris, Konstantinos C.; Charisiadis, Pantelis (My University, 2014)
Balancing the risk between microbial and disinfection by-product exposures in potable water through optimization of disinfectant (chlorine) dosing often proves a difficult task in aging urban drinking-water distribution systems (UDWDS). We hypothesized that geocoded pipe characteristics could improve our understanding of chlorine consumption in a city of a geographic region (Eastern Mediterranean) that has been poorly studied. The main objectives of this study were to (1) determine the UDWDS characteristics (household distance from chlorination tank and pipe leaks) that could explain the spatial variability of residual free chlorine, and (2) investigate the association between water microbial counts and residual chlorine in two areas with contrasting pipe network characteristics (low-risk and high-risk; LRA and HRA). We collected water samples from 150 households in two areas of Nicosia, Cyprus, during winter (air temperatures 0-15°C). Household addresses were linked with geocoded pipe network data, on-site residual chlorine levels, trihalomethanes (THM), and microbiological measurements. No significant difference (p>0.05) in the average free residual chlorine levels was observed between the two areas, despite their documented differences in water age. However, the mean THM concentration in HRA (76 μg/L) was significantly (p<0.001) higher than that in LRA (56 μg/L). Each household's distance from the chlorination tank could explain up to 29% of the variability in free residual chlorine levels for LRA, after adjusting for confounders, such as, total bacterial count (TBC) 22°C/37°C, THM, and pipe leaking incidences; this strength of association did not hold for HRA. Pooling data from both areas, a significant (p<0.05) multivariate model of residual chlorine was constructed, with TBC 37°C being the only significant predictor. Water boards with historically low water microbial counts could apply area-specific residual chlorine monitoring and management schemes within their UDWDS to ensure minimization of total THM formation.
Keywords: Biofilms; Chlorine; Disinfection; Drinking water distribution system; Microbiology; Pseudomonas; Trihalomethanes